The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1111/j.1600-0536.1998.tb05657.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed‐type hypersensitivity to contact allergens in psoriasis

Abstract: The possibility for patch testing procedures to detect contact allergy was examined in 85 hospitalized patients with forms of psoriasis. Exclusion criteria were active lesions on the back, the use of strong topical corticosteroids, methotrexate, cyclosporin and UV therapy. After screening, a group of 47 patients with different forms of psoriasis were selected for patch testing. Personal history, including topical treatment, occupation and domestic circumstances, were reasons to extend the standard series of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1
10

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 8 publications
(5 reference statements)
1
40
1
10
Order By: Relevance
“…The research concerning contact hypersensitivity in psoriasis patients Potato Carrot have not shown univocal results. There are some weakly expressed data about contact hypersensitivity in psoriasis patients contrary to strongly expressed hypersensitivity connected with contact allergens in patients with palmoplantar pustulosis [15][16][17]. Our research shows that there is weakly expressed contact hypersensitivity in psoriasis patients.…”
Section: Discussionmentioning
confidence: 65%
“…The research concerning contact hypersensitivity in psoriasis patients Potato Carrot have not shown univocal results. There are some weakly expressed data about contact hypersensitivity in psoriasis patients contrary to strongly expressed hypersensitivity connected with contact allergens in patients with palmoplantar pustulosis [15][16][17]. Our research shows that there is weakly expressed contact hypersensitivity in psoriasis patients.…”
Section: Discussionmentioning
confidence: 65%
“…Some HSPs could be targets for T cells possessing ␥␦-receptors, which are predominant in skin with various immune disorders. It has been demonstrated that antibodies that reacted with periodontopathic HSPs can be found in serum samples from patients with periodontal disease 9,14,23,24) . These data suggest that HSP-producing chronic infectious bacteria could trigger PPP.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for such exceptional cases include reproducible positive patch test reactions to various metals and analytical results of dental metal testing demonstrating the presence of metals to which the patients are undoubtedly hypersensitive. Dramatic curative effects of allergenic metal elimination have been reported 9,17) . It is valuable to examine the relationship between dental metal allergy and other humoral immune responses to various antigens in patients with PPP.…”
Section: Pustulosis Palmaris Et Plantaris (Ppp) Amentioning
confidence: 99%
See 1 more Smart Citation
“…Deriye temas ederek dermatite neden olan iritan ya da alerjen maddeler psoriasis lezyonlarını tetikleyebilen ekzojen faktörler arasında sayılmaktadırlar. Birçok araştırmacı tedaviye dirençli olan el içi-ayak tabanı gibi lokalizasyonlardaki psoriasis lezyonlarında kontakt dermatitin hastalığı tetikleyen bir faktör olabileceğini ve Koebner fenomeni nedeniyle kontakt dermatit kliniğinin maskelenebileceğini düşünmüşlerdir (1,2). Ayrıca psorisis lezyonlarında dermal papillalar üzerinde ince olan epidermisin bariyer fonksiyonunun tedavide sık kullanılan keratolitik ajanlar nedeniyle bozulması alerjen maddelerin deriye penetrasyonunu kolaylaştırabilir (2).…”
Section: Introductionunclassified